NATUREVOLUTION EFFECTIVE AGAINST CANCER THERAPY– REVIEW (TREATING CANCER DISEASES USING PLANT PRODUCTS) - DR. R. SRINIVASAN; G. LAKSHMANA; B. ANJINAYALU; D. ANIL KUMAR; K. SHALEM RAJU (International Journal of Pharma and Bio Sciences, 2014)
Naturevolution is a term necessary to evaluate ourselves in term metabolism of natural metabolites. Our studies insist on natural products more extremely powerful treatment for cancer cures. The truth is they actually hate people using any form of natural cures for cancer. Mainly anticancer agents are obtained from plants (vincristine, vinblastine, etoposide, paclitaxel, camptothecin, topotecan and irinotecan), marine organisms (citarabine, aplidine and dolastatin 10) and microorganisms (dactinomycin, bleomycin and doxorubicin)some of the fruits and vegetables also has anticancer activity.some of the plant products which are in daily usage are capsaicin (red chilli), diosgenin (fenugreek), 6-gingerol (ginger), ellagic acid (pomegranate), curcumin (turmeric), resveratrol (red grapes, peanuts and berries), genistein (soybean), diallyl sulfide (allium), S-allyl cysteine (allium), allicin (garlic), lycopene (tomato), ursolic acid (apple, pears, prunes), silymarin (milk thistle), anethol (anise, camphor, and fennel), catechins (green tea), eugenol (cloves), indole-3carbinol (cruciferous vegetables), limonene (citrus fruits), beta carotene (carrots), and dietary fiber.in this review the active principle obtained from natural products and novel lead compounds along with mechanism of action has been included.